Peripheral and Spinal Mechanisms Involved in Electro-Acupuncture Therapy for Visceral Hypersensitivity - Tahir, Adnan Hassan; Li, Jia-Jia; Tang, Yong (Frontiers in Neuroscience, 2021)
One of the important characteristic features of clinically significant gastrointestinal disorders is visceral hypersensitivity (VH). Pain sensitization or VH is a big challenge for clinicians and becomes a very thorny work in clinical practices; the therapeutic efficacy for VH results in limited success. A popular second therapy that is being approved for the induction of analgesia and attenuates VH with fewer side effects includes electro-acupuncture (EA). Different peripheral and spinal neurological chemicals, including neurotransmitters, neuropeptides, and cytokines, and different signaling pathways were associated with EA treatment in VH. Despite the higher acceptance of EA, the underlying mechanism still needs to be further explored. In this paper, we review the available literature to find the peripheral and spinal mechanisms involved in EA to relieve VH.